Quality evaluation of four Ferula plants and identification of their key volatiles based on non-targeted metabolomics - Jiang, Meng; Peng, Mengwen; Li, Yuxia; Li, Guifang; Li, Xiaobo; Zhuang, Li (Frontiers in Plant Science, 2024)
Ferula is a traditional, edible, and important medicinal plant with high economic value. The distinction between edible and non-edible Ferula remains unclear. Therefore, in this study, headspace solid-phase microextraction coupled to gas chromatography-mass spectrometry (HS-SPME/GC-MS) and ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) non-targeted metabolomics techniques were used to systematically and comprehensively analyse secondary metabolites in the leaves and roots of four species of Ferula, considering their edibility. A total of 166 leaf volatile organic compounds (VOCs) and 1,079 root metabolites were identified. Additionally, 42 potential VOCs and 62 differential root metabolites were screened to distinguish between edible and non-edible Ferula. Twelve volatile metabolites were specific to F. feurlaeoides, and eight compounds were specific to the three edible Ferula species. The results showed that compounds containing sulphur, aldehydes, and ketones, which produce pungent odours, were the primary sources of the strong odour of Ferula. The root differential metabolites include 13 categories, among which the high concentration group is organic acids, amino acids, terpenoids and fatty acids. The bioactive metabolites and VOCs in the roots exhibited species-specific characteristics. VOCs with various odors were linked to the distribution of root metabolites in both edible and non-edible Ferula plants. The screened root markers may contribute to the formation of characteristic VOCs. This study identified the difference in flavor between edible and non-edible Ferula plants and, for the first time, demonstrated the contribution of the efficacy of Ferula root to the unique flavor of the above-ground parts of Ferula. These results provide a theoretical basis for selecting Ferula for consumption and help evaluate the quality of different species of Ferula. Our findings may facilitate food processing and the further development of Ferula.